TRANSFORMATION OF POSITION AND ROLE OF THE WOMAN IN SOCIETY: PROBLEM ANALYSIS - Armen, A. S. (Anthropological Measurements of Philosophical Research, 2012)
This article is devoted the analysis of of change the role of woman in the different spheres of society’s functioning. Reasons of such transformation are considered in this article. The problems are formulated by author that arising up as a result increases of social activity of women.